Health risks of essential Ni and Fe via consumption of water spinach Ipomoea aquatica collected from Peninsular Malaysia - Chee Kong Yap; Wan Hee Cheng; Koe Wei Wong; Aziran Yaacob; Rozilah Razalai; Chee Seng Leow; Shih Hao Tony Peng; Mohamad Saupi Ismail; Chee Wah Yap; Yuhai He; Moslem Sharifinia; Alireza Riyahi Bakhtiari; et al. (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
The concentrations of Fe and Ni were analyzed in the water spinach Ipomoea aquatica collected from 11 sampling sites (Ara Kuda (2016), Setiawan (2016), Sikamat (2013-2018) and 8 sites in Sepang area (2005-2006)) from Peninsular Malaysia. The range of Fe (mg/kg dw) in the plant samples was 155-775(15.5-77.5mg/kg ww) while the range of Ni(mg/kg dw) was 1.71-20.3(0.17-2.03 mg/kg ww). In assessing the human health risk, the target hazard quotient values for Fe and Ni in Malaysian adults are <1.00. The current results showed no non-carcinogenic risks of Fe and Ni through the consumption of I. aquatica from the 11 sites. Considering the fact that most of the samples were collected from the wild and grown in the uncontrolled drainages, the heavy metal concentrations should be closely monitored in these vegetables.